Comparison of Genome-Wide DNA Methylation Profiles of Human Fetal Tissues Conceived by in vitro Fertilization and Natural Conception - Liu, Ye; Li, Xinzhu; Chen, Songchang; Wang, Li; Tan, Yajing; Li, Xiaocui; Tang, Lin; Zhang, Junyu; Wu, Dandan; Wu, Yanting; Liu, Xinmei; Zhu, Yimin; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Assisted reproductive technology (ART) might induce adverse pregnancy outcomes and increase the risk of metabolic diseases in offspring’ later life with unknow reasons. Here we evaluated the global methylation level and methylation profile of fetal tissue from elective terminations of pregnancy (ETP) after natural conception and multifetal pregnancy reduction (MFPR) after in vitro fertilization and embryo transfer (IVF-ET). Results: Global methylation levels were comparable between the fetal tissue of ETP after natural conception group and MFPR after IVF-ET group. The methylation levels were lower in the hypermethylated regions of the MFPR group than in the ETP group, while the methylation levels were higher in the hypomethylated regions of the MFPR group. Heatmap visualization and hierarchical clustering of the candidate differentially methylated regions (DMRs) showed differences between the DMRs in the ETP and MFPR samples. We identified 196 differentially methylated regions that matched 164 genes between the ETP and MFPR groups. In the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, skeletal system morphogenesis and diabetes mellitus ranked first. Ingenuity Pathway Analysis (IPA) revealed 8 diseases and functional annotations associated with IVT-ET. In the MFPR group, the final validation showed lower methylation levels in gene bodies of bone morphogenetic protein 4 (BMP4), higher methylation levels in the 1st exon and 5’UTR of thyroid peroxidase (TPO), and higher methylation levels in TSS1500 and TSS200 of interleukin 1 beta (IL1B). Conclusions: ART does not alter global DNA methylation level, but influences DNA methylation variation in specific regions of human fetus in the early stage of life. Further studies are warranted to clarify the potential role of DNA methylation alterations in the gene expression profile.